Estratégias de enfrentamento ante a precarização laboral: análise da experiência dos trabalhadores autônomos do setor de turismo na Cidade de Fortaleza - Pontes, Glaucia Rebeca Teixeira de Oliveira (2007)
This study objectifies to evince the process of precarization of labor that autonomous workers from the tourism sector– operators of transport and tourism - in the city of Fortaleza face and their relation with stress at work, emphasizing the coping strategies these professionals are using in the execution of their activities. Our reflection is based on the theoretical referential of Social Psychology, together with stress theories in articulation with socio-historical aspects involved in the phenomena. Methodologically, we used a qualitative approach, recognizing the relevance for the object of analysis. The study was dividedin two moments: in the first, it was used the Inventary of Stress Symptoms for Adults by Lipp (2000) –ISSL, aiming the identification of the level of stress in the respondents.15 workers took part in this stage. The data analysis was carried out according to the correction criteria of the inventory. In the second part, we used the interview. 7 workers participated and the criterion of choice was those who presented stress in their inventories. The analysis of the qualitative material was done through content analysis.The articulation between the precarization process and the development of coping strategies identified in the group studied highlights the necessity to deepen the analysis of the effects of intense transformation of labor reality on the workers.